What Ambulatory Care Managers Need to Know About Examination Room Utilization Measurement and Analysis. Issue 3 (July 2016) - Klarich, Mark J.; Rea, Ronald W.; Lal, Tarun Mohan; Garcia, Angel L.; Steffens, Fay L.
Abstract : Demand for ambulatory care visits is projected to increase 22% between 2008 and 2025. Given this growth, ambulatory care managers need to proactively plan for efficient use of scarce resources (ie, space, equipment, and staff). One important component of ambulatory care space (the number of examination rooms) is dependent on multiple factors, including variation in demand, hours of operation, scheduling, and staff. The authors (1) outline common data collection methods, (2) highlight analysis and reporting considerations for examination room utilization, and (3) provide a strategic framework for short- and long-term decision making for facility design or renovation.